2008
DOI: 10.1142/s0219091508001350
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Non-Performing Loans on Bank's Operating Efficiency for Taiwan Banking Industry

Abstract: The DEA model is applied to analyze the operational efficiency of Taiwan's publiclylisted banks to reveal the influence of the rising non-performing loan ratio (NPLR) on Taiwan's banking industry. After taking into account the NPLR and the different classifications of banks, the respective performances of different types of banks exhibit the following variations and characteristics: the originally more-efficient new private banks significantly fell behind the old public banks in terms of efficiency scores afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…It is evidenced that rapid growth of non-performing loans signals bank failure (Gonzalez, 2005). This proxy is commonly used by Ayuso et al (2004), Jokipii and Milne (2011), Shim (2013), Huang, Ko, and Liu (2004), Liang, Yao, Hwang, and Wu, (2008), Lu and Boateng, (2017), Zheng, Moudud-Ul-Huq, Rahman, and Ashraf (2017), and among others. We also incorporate z -score as an alternative measure of risk for robustness checks in the second part of the fourth section.…”
Section: Data and Variablesmentioning
confidence: 99%
“…It is evidenced that rapid growth of non-performing loans signals bank failure (Gonzalez, 2005). This proxy is commonly used by Ayuso et al (2004), Jokipii and Milne (2011), Shim (2013), Huang, Ko, and Liu (2004), Liang, Yao, Hwang, and Wu, (2008), Lu and Boateng, (2017), Zheng, Moudud-Ul-Huq, Rahman, and Ashraf (2017), and among others. We also incorporate z -score as an alternative measure of risk for robustness checks in the second part of the fourth section.…”
Section: Data and Variablesmentioning
confidence: 99%
“…They drew the conclusion that restructuring generally did not increase the efficiency of the banking system. Liang et al (2008) applied DEA to analyze the efficiency of Taiwan's publicly-listed banks taking into account the influence of the rising non-performing loan ratio. It was found that efficiency scores of the originally more-efficient new private banks significantly fell behind that of the old public banks.…”
Section: Literature Reviewmentioning
confidence: 99%